Pengaruh Social Media Marketing, Online Customer Review Dan Brand Ambassador Terhadap Minat Beli Produk Scarlett Pada Gen Z - Janah, Rismatul; Jannah, Miftahul (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
This research aims to determine the influence of social media marketing, online customer reviews, and brand ambassadors on interest in purchasing Scarlett products among Gen Z. The research method uses quantitative methods. The data used are primary and secondary data. Data was obtained by distributing questionnaires to a sample of 97 respondents. This research uses a purposive sampling method and the analytical tool used is multiple linear regression with the help of the SPSS 29 program. Partial test results show that social media marketing has a significant effect on purchase interest, online customer reviews do not have a significant effect on purchase interest, and brand ambassadors have a significant effect on purchase interest. For simultaneous tests, it shows that social media marketing, online customer reviews, and brand ambassadors have a significant effect on purchasing interest. The coefficient of determination value is 0.469, meaning that the regression model obtained is able to explain that the variables social media marketing, online customer reviews, and brand ambassadors can influence purchasing interest in Scarlett products by 46.9%. Meanwhile, the remaining 53.1% was influenced by other variables not explained in this research.